2022
DOI: 10.1371/journal.pone.0263760
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of antenatal depression and anxiety among women in South Asia: A systematic review & meta-analysis

Abstract: Background Pregnancy is a time of major psychological changes making pregnant women more susceptible to depression and anxiety. Prevalence is higher among women living in Bangladesh, India and Pakistan, compared to high-income countries, due to poor understanding and lack of mental health integration within antenatal care. Antenatal depression/anxiety is associated with adverse outcomes including postnatal depression, low birth weight and impaired fetal development. Existing systematic reviews provided only li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
5
19
0
1
Order By: Relevance
“…It is also possible that the difference is caused by sex-based reporting differences, where females are more likely to report depression related symptoms compared with males [ 33 , 34 ]. Other female specific social determinants of depression related symptoms included intimate partner violence, unplanned pregnancy, male gender preference and poor relationship with in-laws [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the difference is caused by sex-based reporting differences, where females are more likely to report depression related symptoms compared with males [ 33 , 34 ]. Other female specific social determinants of depression related symptoms included intimate partner violence, unplanned pregnancy, male gender preference and poor relationship with in-laws [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among females, differences in mean WBC count between women who had depressive symptoms and those who did not were both significantly different among heterosexuals (Without depressive symptoms: 7. 35 3.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Similar results were reported by George et al (6), focusing on financial difficulties and marital conflicts being a risk factor for antenatal depression. A systematic review conducted by Insan at al (7) has shown various factors like intimate partner violence, unplanned pregnancy, male preference, and poor relationship with in-laws which shows significant association with antenatal depression. In our study, there was a higher incidence of possible antenatal depression among females having son preference in the family though it was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature search was conducted via the electronic databases MEDLINE, Embase, PsycINFO, Scopus and Web of science using keywords and MeSH headings developed with an information specialist (See Additional File 2 for full OVID search strategy). This review relating to perceptions and attitudes forms part of a wider search strategy which also included a second review investigating the social determinants of antenatal depression in South Asia [ 12 ] (see PROSPERO Ref: CRD42020167903). Search results were exported into the reference manager Zotero and duplicates were removed.…”
Section: Methodsmentioning
confidence: 99%